The effect of physical cues on platelet storage lesion - Lihan Cheng; Lu Wang; Shichun Wang; Qi Liu; Ronghua Diao; Chunyan Yao (Hematology)
Background: Platelet concentrates play an important role in clinical treatment such as platelet function disorders and thrombocytopenia. In the process of preparation and storage of platelets, centrifugation, leukofiltration, and agitation will cause morphological changes and impaired function of platelets, which is associated with the increase of platelet transfusion refractoriness, and named as platelet storage lesion (PSL).Method: This paper proposes three major operations (centrifugation, agitation, and leukofiltration) that platelets experience during the preparation and storage process, to explore the effect of physical cues on PSL. The analysis of morphology, metabolism index, and levels of activation markers are used to monitor the quality of stored platelets and definite the role of physical cues in PSL.Result: In this study, centrifugation, leukofiltration and agitation lead to different degrees of platelet activation, with the extension of storage time. At one hour after separation, PSL can be found through structural change, metabolic parameters, and activation markers of platelets. Agitation maintains more cell numbers, better cell morphology, and lower metabolism rate in platelets, and keeps the low activation state of platelets throughout the storage period. The hard centrifugation group showed the highest level of CD62P expression throughout the storage.Conclusion: our results indicate that agitation can mitigate PSL by supplying sufficient O2 during preservation, shear stress may cause PSL immediately after the physical cues were applied; however, hydrostatic pressure induced by filtration is negligible for its effects on PSL. Meanwhile, when the physical cues are big enough, the activation of platelets is irreversible, such as spin at 2000 g. The granule secretion of platelets is a kind of irreversible activation; however, the membrane reorganization of platelets is a kind of reversible activation.